2020
DOI: 10.3390/ijms21176237
|View full text |Cite
|
Sign up to set email alerts
|

Role of Poly [ADP-ribose] Polymerase 1 in Activating the Kirsten ras (KRAS) Gene in Response to Oxidative Stress

Abstract: In pancreatic Panc-1 cancer cells, an increase of oxidative stress enhances the level of 7,8-dihydro-8-oxoguanine (8OG) more in the KRAS promoter region containing G4 motifs than in non-G4 motif G-rich genomic regions. We found that H2O2 stimulates the recruitment to the KRAS promoter of poly [ADP-ribose] polymerase 1 (PARP-1), which efficiently binds to local G4 structures. Upon binding to G4 DNA, PARP-1 undergoes auto PARylation and thus becomes negatively charged. In our view this should favor the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Preliminary data have shown that both conformers are recognized by the nuclear factors, albeit to different extents (in preparation). Evidence that 32R behaves as a regulatory element for KRAS transcription has been provided [ 35 , 37 , 39 , 40 ]. The mechanism by which the gene is regulated is rather complex and recent data suggest that guanine oxidation to 8OG might play a role, in particular under-enhanced oxidative stress, which is typical of cancer cells [ 26 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preliminary data have shown that both conformers are recognized by the nuclear factors, albeit to different extents (in preparation). Evidence that 32R behaves as a regulatory element for KRAS transcription has been provided [ 35 , 37 , 39 , 40 ]. The mechanism by which the gene is regulated is rather complex and recent data suggest that guanine oxidation to 8OG might play a role, in particular under-enhanced oxidative stress, which is typical of cancer cells [ 26 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence that 32R behaves as a regulatory element for KRAS transcription has been provided [ 35 , 37 , 39 , 40 ]. The mechanism by which the gene is regulated is rather complex and recent data suggest that guanine oxidation to 8OG might play a role, in particular under-enhanced oxidative stress, which is typical of cancer cells [ 26 , 39 ]. This is based on the following experimental observations: (i) guanines in 32R tend to oxidize more than isolated guanines; the guanine at the 5′ end of a G-run shows the lowest ionization potential, i.e., the highest tendency for oxidation [ 41 , 42 , 43 ]; (ii) the KRAS gene is responsive to ROS, as it is upregulated when the cellular oxidative stress is increased by H 2 O 2 or by photoactivated porphyrins [ 39 , 44 ]; (iii) pulldown and chromatin immunoprecipitation (ChIP) experiments show that 8OG and G4 co-localize in the same promoter region containing 32R [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcription of oncogenes, like Kirsten Rat Sarcoma Viral Proto-Oncogene (KRAS) and Transformer 2 Beta Homolog (TRA2B), are promoted by hnRNP A1 binding to a G-quadruplex structure in the genes' promoters, utilizing hnRNP A1 DNA binding activity (Paramasivam et al, 2009;Nishikawa et al, 2019). Promotion of KRAS transcription has recently been shown to be regulated by the cell stress response regulator poly (ADP-ribose) polymerase (PARP-1), which itself PARylates hnRNP A1 (discussed below), although the impact of hnRNP A1 PARylation on KRAS transcription, and the function of KRAS expression in the context of oxidative stress are currently unclear (Table 1) (Duan et al, 2019;Cinque et al, 2020). Additionally, hnRNP A1 stabilizes SIRT1 mRNA (Wang et al, 2016); increased abundance of its protein product Sirtuin/SIRT1 prevents progression to cellular senescence, but also de-acetylates hnRNP A1 protein, which negatively regulates oncogenic cell proliferation by modulating alternative splicing of pro-survival mRNAs like PKM (Table 1) .…”
Section: Hnrnp A1 and Transcriptionmentioning
confidence: 99%